Comparative analysis of first-year fingolimod and natalizumab drug discontinuation among Swedish patients with multiple sclerosis. (January 2016) - Frisell, T; Forsberg, L; Nordin, N; Kiesel, C; Alfredsson, L; Askling, J; Hillert, J; Olsson, T; Piehl, F
Background: Natalizumab (NTZ) and fingolimod (FGL) are mainly used second line in relapsing–remitting multiple sclerosis (MS), although pivotal trials included mainly treatment-naïve patients. Objective: This study aims to provide real-world data on safety and discontinuation rates. Methods: Using IMSE, a drug monitoring registry for all newer MS drugs in Sweden, we analysed differences in baseline characteristics and 1-year drug survival for patients registered 2011–2013, initiating treatment with NTZ ( n =640) or FGL ( n =876). Among FGL initiators, n =383 (44%) had previously used NTZ (FGL afterNTZ ). Results: Compared with NTZ, the FGL cohort was older and more often male (36/38 years, 24%/33% males). Baseline Expanded Disability Status Scale was similar across groups, but MS Severity Score was higher in NTZ patients, and Symbol Digit Modalities Test and MS Impact Scale (MSIS-29) was higher in FGL afterNTZ versus FGL NTZ-naïve patients. Proportion on drug after 1 year was high, NTZ=87%, FGL NTZ-naïve =83% and FGL afterNTZ =76%. Adverse events was the most frequent reason for discontinuing FGL (FGL NTZ-naïve =9%, FGL afterNTZ =12%), and was significantly higher than on NTZ (3%). In contrast, the proportion of patients stopping treatment due to lack of effect was more similar: NTZ=4%, FGL NTZ-naïve =3%, FGL afterNTZ =8%. Conclusion: FGL and NTZ were both well tolerated, but FGL less so than NTZ, especially in patients switching to FGL from NTZ. Group differences were not explained by differences in recorded baseline characteristics.